Creative Strategies of Teachers in Teaching PAI and Their Implications on Students' Learning Interest - Imam Jafar (International Journal of Islamic Education Studies, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students’ moral values, spiritual awareness, and ethical behavior. However, maintaining student interest in PAI remains a challenge due to traditional teaching methods, lack of engagement, and competing distractions. This study aims to examine the role of teacher creativity in teaching PAI and its impact on student interest. Using a Systematic Literature Review (SLR) approach, relevant studies from peer-reviewed journals, conference papers, and educational reports published between 2014 and 2024 were analyzed. The review focused on identifying creative teaching strategies, evaluating their effectiveness, and understanding their influence on student motivation and engagement. Findings indicate that strategies such as project-based learning, role-playing, interactive discussions, and multimedia integration significantly enhance student interest and participation. The use of technology further supports personalized and interactive learning experiences, enabling students to connect religious concepts with real-life applications. Despite challenges including limited resources, teacher preparedness, and external distractions, creative teaching consistently promotes better learning outcomes, moral development, and ethical behavior. The study highlights the importance of fostering teacher creativity, integrating innovative methods, and providing institutional support to enhance the quality and effectiveness of PAI in secondary schools. These insights offer practical recommendations for educators and policymakers seeking to improve student engagement and the internalization of Islamic values through creative teaching approaches.